2014
DOI: 10.3892/ijo.2014.2307
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes stem-like properties of laryngeal cancer cell lines by increasing the CD133+ stem cell fraction

Abstract: Evidence indicates that a hypoxic micro-environment plays an essential role in the regulation of cancer stem cells (CSCs). However, whether hypoxia is able to regulate the stem-like biological properties of laryngeal cancer cells remains unknown. In this study, we investigated the influence of hypoxia on the stemness of two laryngeal cancer cell lines, Hep-2 and AMC-HN-8. We cultured the two cell lines under hypoxia and normoxia and examined the influence of hypoxia on the expression of hypoxia-inducible facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…Similarly, Wu et al reported that hypoxia treatment of laryngeal cancer cell lines significantly expanded G0/G1 stage (a fundamental feature of stem cells) and increased the CD133 + CSC subpopulation . They also found that hypoxia increased the mRNA levels of stem cell genes NANOG, OCT4 , and SOX2 , as well as their protein levels . Consistent with the results in laryngeal cancer cells, another group independently reported that hypoxia exhibited similar effects on extending the G0/G1 stage and increasing the CD44 + and ABCG2 + cell populations in prostate cancer cells lines, PC3 and Du145 .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, Wu et al reported that hypoxia treatment of laryngeal cancer cell lines significantly expanded G0/G1 stage (a fundamental feature of stem cells) and increased the CD133 + CSC subpopulation . They also found that hypoxia increased the mRNA levels of stem cell genes NANOG, OCT4 , and SOX2 , as well as their protein levels . Consistent with the results in laryngeal cancer cells, another group independently reported that hypoxia exhibited similar effects on extending the G0/G1 stage and increasing the CD44 + and ABCG2 + cell populations in prostate cancer cells lines, PC3 and Du145 .…”
Section: Introductionmentioning
confidence: 54%
“…Similarly, Wu et al reported that hypoxia treatment of laryngeal cancer cell lines significantly expanded G0/G1 stage (a fundamental feature of stem cells) and increased the CD133 + CSC subpopulation . They also found that hypoxia increased the mRNA levels of stem cell genes NANOG, OCT4 , and SOX2 , as well as their protein levels .…”
Section: Introductionmentioning
confidence: 83%
“…Another study suggested that laryngeal cancer cells, subjected to hypoxia followed by normoxia, exhibited enhanced capacities for proliferation, invasion, sphere, and colony formation in comparison with cells which were maintained consistently under normoxia. These events were associated with an increasing CD133+ fraction denoting regulation of cancer stem cells by hypoxic microenvironments 150 . Moreover, Zhu et al has demonstrated the role of HIF-1 in intermittent hypoxia on promoting the metastatic ability and invasiveness of CD133+ pancreatic cancer stem-like cells 151 .…”
Section: Side Population and Cd133mentioning
confidence: 99%
“…Hypoxia induced CSCs enriched in Hep-2 cells [51] and CD133+ cells isolated from freshly resected laryngeal tumor specimens [21] displayed significantly elevated OKS levels, pointing in their importance as critical CSCs biomarkers for LCa.…”
Section: Oct4 Klf4 and Sox2mentioning
confidence: 99%